2010
DOI: 10.1007/s00726-010-0601-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptative response of nitrogen metabolism in early endotoxemia: role of ornithine aminotransferase

Abstract: Arginine (Arg) and glutamine (Gln) utilization is greatly increased during catabolic stress. While the supply of both amino acids has been advocated in this situation, arginine administration is possibly associated with deleterious effects. From a metabolic point of view, these two amino acids are reciprocal precursors via ornithine aminotransferase (OAT). We hypothesized that OAT plays a key role in the interconversion between Arg and Gln. To test this hypothesis, we evaluated the influence of OAT activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…However, no deficit in the plasma arginine pool, comparable to the metabolic derangements reported in man, was found in these acute models [22], [45][48]. It should however be mentioned that one experimental animal study reported significant changes in the arginine flux in the early stages of endotoxemia [48]. Our new model was based on a pilot observation in mice that plasma arginine concentrations decreased below baseline from 12 hours after the onset of the continuous endotoxin infusion, which is supported by the observations of Braulio et al [31].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, no deficit in the plasma arginine pool, comparable to the metabolic derangements reported in man, was found in these acute models [22], [45][48]. It should however be mentioned that one experimental animal study reported significant changes in the arginine flux in the early stages of endotoxemia [48]. Our new model was based on a pilot observation in mice that plasma arginine concentrations decreased below baseline from 12 hours after the onset of the continuous endotoxin infusion, which is supported by the observations of Braulio et al [31].…”
Section: Discussionsupporting
confidence: 54%
“…In these models, arginine as substrate for NO was identified as key factor in development of the microcirculatory and perfusion disturbances related to endotoxemia. However, no deficit in the plasma arginine pool, comparable to the metabolic derangements reported in man, was found in these acute models [22], [45][48]. It should however be mentioned that one experimental animal study reported significant changes in the arginine flux in the early stages of endotoxemia [48].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Conversely, OAT activity is decreased by glucocorticoids [154,155], and by lipopolysaccharide (LPS) [156]. In mice and rats, it presents circadian variations, with a decrease along the day, by control of the translation step, but with no change in the mRNA levels [17,149,157], and with an effect of the dark/light transitions [158].…”
Section: Localization Of Oatmentioning
confidence: 99%
“…Ventura et al [156] showed that the adaptive response of nitrogen metabolism in early endotoxemia is associated with a physiological inhibition of liver OAT, the latter being responsible for increased Orn in the liver. This OAT inhibition could be considered as a protective mechanism, sparing Orn for other metabolic pathways (Pro and polyamine synthesis).…”
Section: Oat In Health and Diseasementioning
confidence: 99%